THE INFLUENCE OF TEACHER INNOVATION THROUGH STRENGTHENING PROACTIVE PERSONALITY, KNOWLEDGE SHARING, AND CREATIVE SELF-EFFICACY - Sujatmiko Baliarto; Soewarto Hardhienata; Sri Setyaningsih (Yayasan Education and Social Center, 2026)
The effectiveness of school principals' decision-making is critical to improving the quality of education; however, many principals still face challenges in making timely, accurate, and appropriate decisions. This study aims to examine the direct and indirect effects of visionary leadership (X1), trust (X2), and information and communication technology (ICT) literacy (X3) on decision-making effectiveness (Y) among public elementary school principals in Bogor City. The research employed a mixed-methods approach with a sequential, exploratory design, grounded in the POP-SDM framework. The study population comprised 209 public elementary school principals in Bogor City, and 138 respondents were selected via proportional random sampling. Data were collected using Likert-scale questionnaires that had undergone validity and reliability testing and were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results demonstrated that visionary leadership (β=0.224; p<0.05), trust (β=0.246; p<0.05), and ICT literacy (β=0.216; p<0.05) each exerted a direct positive and significant effect on decision-making effectiveness. Furthermore, trust and ICT literacy partially mediate the influence of visionary leadership on decision-making effectiveness. The research model explained 51.6% of the variance in decision-making effectiveness. These findings confirm that the integrated strengthening of visionary leadership, trust, and ICT literacy can enhance principals' decision-making effectiveness.